TLR7 Promotes Tumor Progression, Chemotherapy Resistance, and Poor Clinical Outcomes in Non–Small Cell Lung Cancer - Chatterjee, Saradiya; Crozet, Lucile; Damotte, Diane; Iribarren, Kristina; Schramm, Catherine; Alifano, Marco; Lupo, Audrey; Cherfils-Vicini, Julien; Goc, Jeremy; Katsahian, Sandrine; Younes, Mohammad; Dieu-Nosjean, Marie Caroline; et al. (Cancer research (Chicago, Ill.), 2014)
Toll-like receptors (TLR) recognize pathogen molecules and danger-associated signals that stimulate inflammatory processes. TLRs have been studied mainly in antigen-presenting cells, where they exert important immune regulatory functions, but they are also expressed by epithelial tumor cells, where they have been implicated in tumor progression. In this study, we demonstrate that the injection of TLR7 agonist in NOD/SCID mice, in C57BL/6 wild-type, and TLR7-deficient mice grafted with lung adenocarcinoma tumor cells leads to increased tumor progression and chemotherapeutic resistance. In patients with non–small cell lung cancer, expression analyses revealed that high TLR7 expression was strongly associated with resistance to neoadjuvant chemotherapy and poor clinical outcomes. Our findings delineate a crucial role for TLR7 in lung cancer physiopathology. Cancer Res; 74(18); 5008–18. ©2014 AACR.